2011
DOI: 10.1021/la2027779
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of Ultrathin Polymer Films in the Melt Probed by Dielectric Spectroscopy and Second-Harmonic Generation

Abstract: We studied the adsorption kinetics of supported ultrathin films of dye-labeled polystyrene (l-PS) by combining dielectric spectroscopy (DS) and the interface-specific nonlinear optical second harmonic generation (SHG) technique. While DS is sensitive to the fraction of mobile dye moieties (chromophores), the SHG signal probes their anisotropic orientation. Time-resolved measurements were performed above the glass transition temperature on two different sample geometries. In one configuration, the l-PS layer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 35 publications
7
88
1
Order By: Relevance
“…Adoption of various conformations by polymer chains (tails, loops, trains [31]) at the interfaces with solid surfaces were found also of importance for predicting interfacial polymer properties [3,[32][33][34]. Theodorou and coworkers [3,29] showed that polymer chains close to an attractive solid surface are pronouncedly flattened, or else more parallel to the surface, as compared to those away from the surface, this result coming in agreement with respective experimental studies [20,35]. Finally, Bitsanis and Brinke [32] and Harmandaris and coworkers [3,33,34] pointed to the polymer chain length as a crucial parameter for adoption of different conformations of polymers adsorbed on solid surfaces and of polymer confined between solid surfaces, respectively.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Adoption of various conformations by polymer chains (tails, loops, trains [31]) at the interfaces with solid surfaces were found also of importance for predicting interfacial polymer properties [3,[32][33][34]. Theodorou and coworkers [3,29] showed that polymer chains close to an attractive solid surface are pronouncedly flattened, or else more parallel to the surface, as compared to those away from the surface, this result coming in agreement with respective experimental studies [20,35]. Finally, Bitsanis and Brinke [32] and Harmandaris and coworkers [3,33,34] pointed to the polymer chain length as a crucial parameter for adoption of different conformations of polymers adsorbed on solid surfaces and of polymer confined between solid surfaces, respectively.…”
Section: Introductionsupporting
confidence: 72%
“…More specifically, according to recent studies on adsorbed polymers [6,20,21] there may exist two populations of chain segments at interfaces which can be considered responsible for the molecular mobility recorded in BDS as the interfacial a int process, i.e. (a) extended tails with bulk-like density but reduced mobility and cooperativity (Scheme 1a), and (b) flattened chain segments which form the inner quite dense region due to multiple contact points with the silica surface (loops, Scheme 1a).…”
Section: Interpretation In Terms Of Modelsmentioning
confidence: 99%
See 3 more Smart Citations